COVID-19 Armenia High Frequency Survey Brief, February 2021 - Fuchs Tarlovsky, Alan (World Bank, Washington, DC, 2021)
This report summarizes the main findings from the Coronavirus (COVID-19) Armenia high frequency survey, wave 1, surveys I and II (COVID-19 AHFS-1 (I & II)) as of February 2021.